Ordering the Rise: Indonesia’s Normative Engagement with China and the Constitution of Asia-Pacific International Society, 2018–2025 - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Ronna Rihadatul Aisy; Fatin ‘Atikah Sandy (Randwick International of Social Science Journal, 2026)
Indonesia’s decision to upgrade defense engagement with China in early 2025, culminating in the first ministerial “2+2” joint foreign and defense dialogue that China has established with any country, raises a puzzle for mainstream explanations of Southeast Asian security behavior. Why would a self-described middle power deepen military cooperation with the region’s predominant rising power while simultaneously sustaining expansive security ties with the United States and other partners? This study addresses that puzzle through the English School of international relations specifically the tradition of Hedley Bull (1977) and Barry Buzan (2004) which conceptualizes international society as a normative order sustained by primary institutions: sovereignty, diplomacy, balance of power, great power management, and international law. We argue that Indonesia’s defense cooperation with China between 2018 and 2025 was not reducible to hedging as an instrumental posture, nor to constrained accommodation. Instead, Indonesia pursued normative engagement as an order-constituting practice: institutionalizing diplomacy through regularized mechanisms, reaffirming sovereignty and non-interference, preserving balance through non-exclusive partnerships, and keeping international law claims alive through persistent UNCLOS-centered diplomacy. We demonstrate that Indonesia performed a form of middle-power facilitative management, constructing institutional pathways through which a rising great power is drawn into consultative habits, and specify the scope conditions governing this mechanism. The case extends Bull’s concept of great power management by identifying a previously undertheorized actor type: the middle power as order-constituting agent.